Hermeneutic philosophies of social science - Babich, Babette E., 1956- (De Gruyter, 2017)
Hermeneutic philosophies of social science offer an approach to the philosophy of social science foregrounding the human subject and including attention to history as well as a methodological reflection on the notion of reflection, including the intrusions of distortions and prejudice. Hermeneutic philosophies of social science offer an explicit orientation to and concern with the subject of the human and social sciences. Hermeneutic philosophies of the social science represented in the present collection of essays draw inspiration from Gadamer's work as well as from Paul Ricoeur in addition to Michel de Certeau and Michel Foucault among others. Special attention is given to Wilhelm Dilthey in addition to the broader phenomenological traditions of Edmund Husserl and Martin Heidegger as well as the history of philosophy in Plato and Descartes. The volume is indispensible reading for students and scholars interested in epistemology, philosophy of science, social social studies of knowledge as well as social studies of technology.